Metagenetic analysis of gut microbial community of Malaysian mahseer Tor tambroides (Bleeker, 1854) (Cyprinidae) and its probiotics potential - Tan, Chun Keat (2017)
Gut microbiota in vertebrate is complex and contains abundant of diverse beneficial microorganisms important for a dynamic host-microbe interaction. Some of these bacteria may have probiotics properties. In this study, the gut microbiota in wild and captive T. tambroides was identified through metagenetic sequencing of 16S rDNA V3-V4 hypervariable regions using Illumina MiSeq. The sequencing data were analyzed using Quantitative Insights into Microbial Ecology (QIIME). Bacteria were isolated from gut of T. tambroides to evaluate its safety and examined for its probiotics properties. These selected potential probiotics were fed to T. tambroides followed by challenge test to evaluate its effects on growth and disease resistance against Aeromonas hydrophila. The metagenetic analyses showed that the gut microbiota in T. tambroides was dominated by Firmicutes, Proteobacteria, Fusobacteria and Bacteroidetes. Wild T. tambroides gut contained Cetobacterium sp. (24.9%), unknown genus from Peprostreptococcaceae family (11.0%), Bacteroides sp. (10.1%), PSB-M-3 from Erysipelotrichaceae family (7.89%) and Vibrio sp. (5.4%). Captive T. tambroides gut contained Cetobacterium sp. (27.9%), Citrobacter sp. (10.0%), unknown genus from Peptostreptococcaceae family (8.2%), unknown genus from Aeromonadaceae family (8.2%) and Turicibacter sp. (7.0%). The results showed that Cetobacterium sp. is the core microbiota in T. tambroides gut. Function of this bacterium in T. tambroides gut needed to be determined. Three Aeromonas sp., two Bacillus sp., two Lysinibacillus spp., and one Pseudomonas sp. were successfully isolated and identified from the wild T. tambroides gut sample. Both Bacillus sp. and Pseudomonas sp. showed quorum sensing inhibition activities while only Pseudomonas sp. showed mild antimicrobial activity against A. hydrophila. These two bacteria were selected for probiotics feeding experiment. Nevertheless, there was no significant difference in growth of T. tambroides fed with these probiotics. The T. tambroides juveniles were then challenged with A. hydrophila by intra-peritoneal injection after the probiotics feeding experiment. Both Bacillus sp. and Pseudomonas sp. appeared to be able to improve disease resistance of T. tambroides juveniles against A. hydrophila infection. Lower mortality was observed in fishes treated with Bacillus sp. and Pseudomonas sp. as compared to positive control. Lysozyme activities in T. tambroides juveniles fed with Bacillus sp. were significantly higher (P<0.05) than other treatments. In conclusion, Cetobacterium sp. is a core gut microbiota in T. tambroides. The other important gut microbiota in T. tambroides may include Bacteroides sp., Citrobacter sp., Turicibacter sp. and Bacillus sp. Bacillus sp. and Pseudomonas sp. isolated in this study showed QSI activity. Bacillus sp. could enhance the innate immune system of fishes by increase lysozyme activity in blood serum. Both Bacillus sp. and Pseudomonas sp. have the potential to be use as probiotics in T. tambroides aquaculture to improve disease resistance and immune system of fishes.